Instructional Sequences of English Language Teachers: An Attempt to Describe Them - José Aldemar Álvarez (Asociación Colombiana de Profesores de Ingles, 2008)
This article reports on the results of a study carried out at Universidad de la Salle which aimed to identify the instructional sequences of six teachers of the "Licenciatura en lengua castellana, inglés y francés". Data were collected through observations, teachers' logs and interviews. Findings show that teachers articulate their instructional sequences guided by stages such as practice, presentation, production, evaluation and homework check.